Quadratus Lumborum Block versus Transversus Abdominis Plane Block for Postoperative Analgesia - Khan, Adeela; Saqib, Najm us; Anjum Anwar Qadri; Abid Khan; Humayun Munir Tarar; Usman Ejaz Malik (Pakistan Armed Forces Medical Journal, 2025)
Abstract Objectives: To determine the efficacy of transversus abdominis plane block and quadratus lumborum block in pediatric lower abdominal surgeries. Study Design: Quasi-experimental study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan to Jul 2023. Methodology: Forty-eight pediatric patients scheduled for unilateral repair of inguinal hernia under general anesthesia were enrolled in the study after random distribution in two groups, Group-T (Transversus Abdominis Plane Block) and Group-Q (Quadratus Lumborum Block). Postoperative pain intensity was evaluated with the Face, Legs, Activity, Cry, and Consolability Scale. Results: There were 48 patients in the trial, with no discernible differences in demographics, American Society of Anaesthesiologists score, surgery type, or duration. In the first 24 hours following surgery, considerably fewer patients in the Quadratus Lumborum Block Group than in the Transversus Abdominis Plane Block Group needed analgesia (p-value <0.05). The one, four, six, and twenty-four hours Face, Legs, Activity, Cry, and Consolability Scale were determined to be lower in Group-Q compared to Group-T (p-value <0.05). Parent satisfaction scores inquired upon on a scale of 1-10, which turned out to be greater in Group–Q 9.00(9.00-8.00) as compared to Group-T 8.00(9.00-7.25), which was statistically significant (p-value =0.006). Conclusions: This study concluded that transversus abdominis plane block is less effective than quadratus lumborum block for pain relief.